Perancangan sistem informasi penjualan Garam Industri menggunakan PHP dan MYSQL di CV Bintang Indo Prakasa Bandung - Pratama, Risma; Nulhakim, S.E, M.M, Lukman (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2021)
The purpose of this study is to analyze, design and build an industrial salt sales information system using PHP and MySQL at CV Bintang Indo Prakasa Bandung. The research method used in collecting the required data is using descriptive analysis methods, such as direct observation of the system that is running or observation, interviews. The software development method uses waterfall modeling. From the research conducted, it was found that the sales information system currently running at CV Bintang Indo Prakasa Bandung still uses a manual sales recording system. Therefore, a new information system was created using a website-based sales system to overcome the problems that occurred. With the use of this information system, it is expected to increase sales transactions that are neatly detailed. The suggestions given are (1) Adding the necessary tools and facilities such as computers, internet networks, and also web hosting, so that this system can run well. (2) Improving the quality of human resources to apply this system. (3) Re-develop the program that has been made so that the results obtained can be better. Keywords: Sales Information System, PHP, MySQL